Blood contact properties of ascorbyl chitosan - Yalinca, Z.; Yilmaz, E.; Taneri, B.; Bullici, F.; Tuzmen, S. (Taylor & Francis Ltd, 2013)
Ascorbyl chitosan was synthesized by heating chitosan with ascorbic acid in isopropanol. The products were characterized by FTIR and C-13 NMR spectroscopies, SEM, and elemental analysis. Blood contact properties of ascorbyl chitosans were evaluated. The ascorbyl chitosans demonstrated to have increased lipid-lowering activity in comparison to chitosan alone upon contact with human blood serum in in vitro conditions. Furthermore, the total cholesterol/HDL ratio was improved towards the desirable ideal values after three hours contact with ascorbyl chitosan samples. The lipid-lowering activity increased with ascorbyl substitution. The inherent nonspecific adsorption capability of chitosan due to its chelating power with several different functional groups was exhibited by ascorbyl chitosans as well. This behavior was exemplified in a simultaneous decrease in the total iron values of the volunteers together with lower lipid levels. Furthermore, ascorbyl chitosans were observed to have less hemocompatibility but increased anticoagulant activity when compared to chitosan alone. Additional in vivo studies are necessary to support these results and to investigate further the advantages and disadvantages of these materials to prove their safety prior to clinical applications.
Keywords: blood-biomaterial interaction; chitosan; ascorbic acid (Vitamin C); blood compatibility; hypocholesterolemic effect; anticoagulant; iron removal; chelation